Peningkatan Hasil Belajar Siswa SMA Negeri di Lubuklinggau Menggunakan Laboratorium Virtual : (Improved Learning Outcomes of State Senior High School Students in Lubuklinggau Using Virtual Laboratories) - Riska Lisa; Indawan Indawan; Bonita Hirza (BIODIK, 2022)
This study aims to determine the increase in student learning outcomes of Lubuklinggau State High School students using a Virtual Laboratory in class XI MIA in the even semester of the 2019/2020 academic year on the Excretion System material. Methods: The sample of this study was 133 students, consisting of 68 control class students and 65 experimental class students, selected using simple random sampling technique. The design used is the pre-test and post-test control group design. Quantitative research data in the form of students' cognitive learning outcomes, namely pre-test scores and post-test scores. Results: The results showed that there was a significant increase in learning outcomes using a virtual laboratory as seen by the Independent t test (sig 0.000 < 0.05) and the sample paired t test to see the effect of using a virtual laboratory in the experimental class (sig 0.000 <0, 05). This means that using a virtual laboratory can have an influence on student learning outcomes in the experimental class. Conclusion: There is an increase in student learning outcomes of SMA Negeri Lubuklinggau by using a Virtual Laboratory. Key words: Learning Outcome, Virtual Laboratory AbstrakÂ  Penelitian bertujuan untuk mengetahui peningkatan hasil belajar siswa SMA Negeri Lubuklinggau menggunakan Laboratorium Virtual pada kelas XI MIA semester genap tahun ajaran 2019/2020 pada materi Sistem Eksresi. Metode: Sampel penelitian ini berjumlah 133 siswa, terdiri dari 68 siswa kelas kontrolÂ  dan 65 siswa kelas eksperimen, dipilih menggunakan teknik simple random sampling. Desain yang digunakan yaitu desain pre-test and post-test control group design. Data penelitian kuantitatif berupa hasil belajar kognitif siswa yakni nilai pre-test dan nilai post-test. Hasil: Hasil penelitian menunjukkan terdapat peningkatan yang signifikan terhadap hasil belajar menggunakan laboratorium virtual dilihat dengan uji Independent t test (sig 0,000 < 0,05) dan uji sample paired t test untuk melihat pengaruh penggunaaan laboratorium virtual pada kelas eksperimen (sig 0,000<0,05). Artinya dengan menggunakan laboratorium virtual dapat memberikan pengaruh terhadap hasil belajar siswa pada kelas eksperimen. Kesimpulan: Terdapat peningkatan hasil belajar siswa SMA Negeri Lubuklinggau dengan menggunakan Laboratorium Virtual. Kata kunci: Hasil Belajar, Laboratorium Virtual.